Teaching strategies in music education teacher training - Márquez Rangel, José Antonio (Universidad Francisco de Paula Santander, 2017)
Music in recent times has taken over different spaces and has become a key element in various innovative concepts referred to some topics as in the case of education, which focuses its interest in music pedagogy and from there arises as an intention: to reveal some strategies for teaching in the career of music education at the Instituto Pedagógico Rural Gervasio Rubio of the Universidad Pedagógica Experimental Libertador. In effect, through the theoretical contribution, some strategies are proposed that converge in an active, pro-active and creative pedagogical action for teaching in the different specialty chairs of the music education career, offering with it methods and tools so that the future music education teacher can re-invent the teaching and learning process to guarantee success and therefore quality in the formation and training of those interested in the music education career. Aspects that are achieved by keeping in mind that music is one of the most important areas within the formation of individuals.